Clinical profile of dengue fever infection in King Abdul Aziz University Hospital Saudi Arabia - Ahmed, Maimoona M (The Journal of Infection in Developing Countries, 2010)
Background: The study aimed to compare the clinical profile of all patients diagnosed with dengue viral infection at King Abdul Aziz University Hospital (KAAUH), during 2005-2008. Methodology: This retrospective study included 147 patients infected with dengue virus, age ≤ 16 years. Laboratory and haematological data were included. Results: Two peaks of infection occurred during 2006 and another two in 2008. Common clinical symptoms were fever, vomiting, and abdominal pain. Common haematological abnormalities were thrombocytopenia and leucopoenia. Differences existed between the years in the percentage of patients with fever, elevated alanine aminotransferase (ALT), direct bilirubin, lactate dehydrogenase (LDH), fibrin degradation products (FDPs), and haemoglobin (Hb) levels. Differences were found in nationalities between the years, but patient nationality had no effect on disease incidence. Differences were noted in the percentages of patients' immunoglobulin M (IgM) and polymerase chain reaction (PCR) positive. There was a slight inverse correlation of IgM positive with patient age. PCR, fever, ALT, direct bilirubin, LDH, FDPs, Hb, blood transfusion, and platelet transfusion showed no correlation with age or nationality. In 2005, all the patients survived, but there were 4.55%, 25%, and 2.7% deaths during 2006-2008. Conclusions: Significant differences in the clinical presentation of dengue virus (DENV) infection, indicative of a variation in disease severity from dengue fever (DF) to dengue hemhorrhagic fever (DHF)/dengue shock syndrome (DSS), were noted over the years. Possible reasons are infection with different serotypes, concurrent/sequential infection of more than one serotype, and differences in host immune responses associated with host genetic variations.